La universidad entre luces y sombras en la experiencia pedagógica emancipatoria de Mauricio Amílcar López - Sonia Elizabeth Riveros; Alberto Martinez Boom (Espacios en Blanco. Serie Indagaciones)
We present a postdoctoral research advance that recovers the pedagogical project of Mauricio Amílcar López and its link with the thought of Latin American integration and liberation. We are concerned about the present that the university is going through and the pedagogical practices that take place there in a current situation that requires, on the one hand, a renewal of teaching methods, other ways of connecting with the outside and between the members of the pedagogical community and, on the other hand, , the constant tension of incorporating new experiences in relation to knowledge and practices that are up to the task of different contexts. Faced with multiple concerns, we ask ourselves about the meaning of recovering a philosophical and pedagogical thinking located in the 70s and its relationship with the experience of our time; what were the conditions of existence of his emancipatory and democratizing discourse; that this Argentine intellectual makes possible for us in the face of the visible and describable of the present temporality.